Association between medial temporal lobe atrophy on CT and parietotemporal uptake decrease on SPECT in Alzheimer's disease. Issue 4 (1st October 1997) - Lavenu, Isabelle; Pasquier, Florence; Lebert, Florence; Jacob, Bruno; Petit, Henri
Abstract : OBJECTIVES: Alzheimer's disease is the most frequent cause of degenerative dementia. Despite the available diagnostic criteria, improvement of diagnosic accuracy is still required. The aim of this prospective study was to assess in a large population of patients referred to a memory clinic the diagnostic value of the combination of medial temporal lobe atrophy on temporal oriented CT and decreased temporoparietal uptake on HMPAO single photon emission tomography (SPECT). METHODS: The study was conducted in 125 patients aged 51-93: 64 with probable Alzheimer's disease (Mean (SD) mini mental state examination (MMSE)=18.34 (6.93)), duration of disease=6.48 (2.93) years, 13 possible Alzheimer's disease (MMSE=21.58 (5.48), duration of disease=6.08 (2.56)), 48 patients with miscellaneous memory disorders (MMSE=21.98 (6.10), duration the disease = 6.85 (3.91)). RESULTS: For the diagnosis of probable Alzheimer's disease, the sensitivity of this association was 0.56, the specificity 0.93, the positive predictive value 0.95, and the negative predictive value 0.45. The diagnosic accuracy was 0.68. Both medial temporal atrophy and parietotemporal decrease in uptake were present in four of 13 patients with possible Alzheimer's disease and 11 of 48 with miscellaneous memory disorders. The association was absent in 27 of 29 patients with frontotemporal dementia. In mild stages (MMSE>18; n = 32), the sensitivity of the association was 0.34, the specificity 0.93, the positive predictive value 0.85, and the negative predictive value 0.57. The diagnosic accuracy was 0.53. CONCLUSION: This association, although not sensitive, helps to select patients with high probability of Alzheimer's disease at an early stage which can be of interest for clinical and research purposes.